Antecedents of management accounting practices and hotel performance: evidence from Malaysian Borneo States / Salumah Nain, Rasid Mail and Nelson Lajuni - Nain, Salumah; Mail, Rasid; Lajuni, Nelson (Universiti Teknologi MARA, 2022)
Management accounting practices remain one of the crucial issues in management accounting research. However, little is known about management accounting practices in the hotel industry in East Malaysia, particularly Sabah, Sarawak, and the Federal Territory of Labuan compared to those in West Malaysia (Peninsular Malaysia States). The hotel sector is the heartbeat of the tourism industry as one of the main contributors of revenues in these states that fill up the states’ coffers. Furthermore, the questions on what factors contribute to management accounting practices are still debatable and varied. Hence, this research aimed to investigate the antecedent factors that contribute to management accounting practices and to examine the effects of management accounting practices in hotel performance. Moreover, rapid growth in the economic system has changed the needs of business enterprises. These changes are accelerated with innovation in technology, the intensifying of market competition, and hotel size. Therefore, managers need to be fully equipped with the latest accounting information for making better business decisions to maximize their performance. We expect this study to contribute to the theoretical and practical aspects of antecedent of management accounting practices to firm performance that will become valuable to many stakeholders and policymakers. Future studies should adopt different approaches, e.g. adopting a qualitative approach or multi-group analysis to enrich the current literature on management accounting practices.